Pengaruh Budaya dan Kompetensi terhadap Kinerja Pegawai dengan Jiwa Sportifitas dan Kewirausahaan sebagai Variabel Moderasi pada Dinas Pemuda dan Olahraga Provinsi Jambi - M, Zulkifli; Lubis, Tona Aurora; Masriani, Ida (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the influence of organizational culture and employee competency on employee performance with sportsmanship and entrepreneurship as moderating variables at the Jambi Province Youth and Sports Office. The research method used is quantitative explanatory with a causality approach. Data were collected through questionnaires distributed to 89 employees, and data analysis was carried out using Partial Least Squares (PLS). The results showed that organizational culture had a positive and significant effect on employee performance, while employee competency had a negative effect. Sportsmanship and entrepreneurship did not moderate the relationship between organizational culture and employee competency on employee performance at the Jambi Province Youth and Sports Office.